2020
DOI: 10.1002/jor.24878
|View full text |Cite
|
Sign up to set email alerts
|

Gait mechanics are influenced by quadriceps strength, age, and sex after total knee arthroplasty

Abstract: Although most patients are satisfied with outcomes after total knee arthroplasty (TKA), many retain preoperative altered gait mechanics. Identifying patient characteristics associated with gait mechanics will improve rehabilitation strategies and enhance our understanding of movement disorders. Therefore, the purpose of this study was to identify which patient characteristics are related to gait mechanics in the surgical limb during walking post‐TKA. Patient characteristics included age, body mass, sex, quadri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Quadriceps strength has been shown to affect the biomechanics (kinematics and kinetics) of the knee joint during gait in patients with TKA [8,9] and has been significantly correlated with gait function [10][11][12][13]. Furthermore, several intervention studies have revealed that the rehabilitation programs focused on quadriceps strength effectively improve gait function in patients who undergo TKA [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Quadriceps strength has been shown to affect the biomechanics (kinematics and kinetics) of the knee joint during gait in patients with TKA [8,9] and has been significantly correlated with gait function [10][11][12][13]. Furthermore, several intervention studies have revealed that the rehabilitation programs focused on quadriceps strength effectively improve gait function in patients who undergo TKA [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies do demonstrate gait analysis parameters that are associated with clinical outcomes after total knee arthroplasty. 8,34,35 Quadriceps weakness, 8,10 gait speed, 8,10,36 cadence, 33 step length, 33 have all been identified as related to outcomes after TKA. However, the correlation of 3D kinematic or kinetic data with clinical outcomes after total knee arthroplasty is sparse in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…6e8 Patients after TKA do exhibit a decreased arc of motion with stair climbing 9 and compensatory changes at the hip and ankle. 10 Thus, the biomechanics of the lower extremity may be altered in patients after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…The lower limb prosthesis was worn much like an article of clothing, and there was almost no difference in muscle strength between the affected limb and the healthy limb. Our research objects were patients who had recently undergone surgical treatment; at this time, the strength of the quadriceps femoris muscles and hamstring muscles of the affected side was significantly lower than that of the healthy side [19]. The difference in postoperative muscle strength may be an important factor affecting the gait changes of patients.…”
Section: Knee Joint Weight Changes and Gait Analysismentioning
confidence: 99%